Pressure- and composition-induced structural quantum phase transition in the cubic superconductor (Sr, Ca)3Ir4Sn13. - Klintberg, L; Goh, S; Alireza, P; Saines, P; Tompsett, D; Logg, P; Yang, J; Chen, B; Yoshimura, K; Grosche, F (2012)
We show that the quasi-skutterudite superconductor Sr(3)Ir(4)Sn(13) undergoes a structural transition from a simple cubic parent structure, the I phase, to a superlattice variant, the I' phase, which has a lattice parameter twice that of the high temperature phase. We argue that the superlattice distortion is associated with a charge density wave transition of the conduction electron system and demonstrate that the superlattice transition temperature T(*) can be suppressed to zero by combining chemical and physical pressure. This enables the first comprehensive investigation of a superlattice quantum phase transition and its interplay with superconductivity in a cubic charge density wave system.